EXPERIENTIAL LEARNING AND ITS RELATIONSHIP TO EVALUATIVE THINKING SKILLS AMONG CHEMISTRY TEACHERS - Aseel Assi Oudah Almasoudy (Scholars Digest Publishing, 2025)
The aim of the current research is to identify experiential learning and its relationship to the evaluative thinking skills of chemistry teachers. The research sample included (30) male and female teachers from middle, middle, and secondary day schools in the center of the Holy Karbala Governorate. To achieve the objectives of the research, the researcher prepared two measures, the first was "(for experiential learning) And another (for evaluative thinking skills) after reviewing previous relevant theories and studies, as the experiential learning scale included (48) items, while the evaluative thinking skills scale in its final form included (45) "items distributed over" three skills, which are (setting benchmarks, Evaluating "evidence" and proofs, "identifying" fallacies). The researcher verified the psychometric properties of the two research tools, which are: honesty and reliability. Validity was verified in two ways: face validity and construct validity. Reliability was extracted for the experiential learning scale and the thinking skills scale. Evaluation using the retest method and the Cronbach equation. The researcher reached the following results.
Keywords: Experiential Learning, Evaluative Thinking Skills.